2013
DOI: 10.1149/2.004308jes
|View full text |Cite
|
Sign up to set email alerts
|

Single-Piece Solid-Contact Polymeric Membrane Ion-Selective Electrodes for Silver Ion

Abstract: Single-piece solid-contact polymeric membrane Ag + ion-selective electrodes (ISEs) have been fabricated based on conducting polymer poly(3-octylthiophene) (POT) dissolved into the Ag + ion-selective membrane. The effects of the amounts of POT on the potential responses of the single-piece solid-contact Ag + -ISEs were investigated in detail. Results indicate that the single-piece solid-contact Ag + -ISE with 10 wt% POT displays excellent reproducibility and stability of the potential response. The linear range… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…In this work, the compound, o-xylylenebis(N, N-diisobutyldithiocarbamate), was chosen as Ag + ionophore, since it shows very high selectivity toward Ag + [29][30][31], as compared with other Ag + ionophores [32,33]. This means that the proposed ionophorebased solid-contact Ag + -ISE may be useful for monitoring the dissolution of Ag NPs in complex background solutions.…”
Section: Characterization Of the Mesoporous Carbon-based Solid-contac...mentioning
confidence: 99%
“…In this work, the compound, o-xylylenebis(N, N-diisobutyldithiocarbamate), was chosen as Ag + ionophore, since it shows very high selectivity toward Ag + [29][30][31], as compared with other Ag + ionophores [32,33]. This means that the proposed ionophorebased solid-contact Ag + -ISE may be useful for monitoring the dissolution of Ag NPs in complex background solutions.…”
Section: Characterization Of the Mesoporous Carbon-based Solid-contac...mentioning
confidence: 99%
“…The group of Qin found that 10% POT can be freely dissolved in the membrane to fabricate ion-selective electrodes for silver ions, with attractive detection limits . The key drawback of this material is the known sensitivity to light.…”
Section: Potentiometrymentioning
confidence: 99%
“…The group of Qin found that 10% POT can be freely dissolved in the membrane to fabricate ion-selective electrodes for silver ions, with attractive detection limits. 32 The key drawback of this material is the known sensitivity to light. The old puzzle of why drop cast, electrically neutral POT layers can give such excellent behavior as intermediate transducing layers in potentiometric was unravelled by the groups of De Marco and Bakker.…”
mentioning
confidence: 99%
“…Currently solid contact ISEs are based on conducting polymers such as PEDOT: PSS and POT . Other constructions are based on molecular redox couples and other materials like gold , platinum and C60 …”
Section: Introductionmentioning
confidence: 99%